Pengaruh Related Party Transaction Terhadap Kinerja Perusahaan - Dwi Ermayanti Susilo; Dyah Ayu Purwaning Tyas (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2020)
This study aims to determine the effect of related party transactions on company performance in food and beverages companies listed on the Indonesia Stock Exchange 2015 - 2019. The population of this study are food and beverages companies listed on the Indonesia Stock Exchange 2015-2019. Sample selection through Purpose Sampling was selected by 6 companies with the criteria as the research sample so that the observation data amounted to 27. The data analysis technique used in this study is multiple linear regression. The results of this study indicate that Sales of Related Parties have a positive and significant effect, indicated by the t value of 12,798 and the sig value of 0,000; Purchases of related parties have no effect, indicated by the t value of -8,092 and a sig value of 0,000.